LAW POLITIC OF ADMINISTRATIVE COURT JUDICATURE IN INDONEESIA - Wahyu Mukti Beny Setiyawan; Fitriya Desi Wulandari (UNISSULA, 2019)
Law politic present at the point of encounter between living realism and the demands ofidealism. Political law concerns on an ideal or hope, then there is a legal vision that is setin advance, then the form and content of the law are built to realize that vision. Theurgency existence of administrative justice in realizing the rule of law encourages thegovernment to establish a legal system in the field of administrative justice through theestablishment of Law Number 51986 about State Administrative Courts, which is thefoundation for the establishment of a State Administrative Court in Indonesia. In theexplanation of Law Number 5 of 1986 stated that the State Administrative Court was heldin order to provide protection to the people seeking justice, which felt themselves to beharmed by a State Administrative Decision. Principly, a country is expected to giveprotection for the human rights of its citizens